Wielki festyn ludowy. (Wejherowo : [s.n.], 1948)
Afisz inf. o festynie wraz z jego programem, który miał miejsce w Rumi 18.07.1948 r.
Keywords: Rumia (Polska) -- 1945-1970 -- druki ulotne; Rumia (Polska) -- 1945-1970 -- plakaty; Rumia (Polska) -- 1945-1970 -- źródła